Pengaruh Media Sosial TikTok terhadap Kreativitas Mahasiswa Komunikasi dan Penyiaran Islam IAIN Sorong - Anggraini, Rina; Sudrimo, Sella Nofriska (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2025)
This study aims to analyze the influence of TikTok social media usage on the creativity level of students in the Islamic Communication and Broadcasting (KPI) Study Program at IAIN Sorong. As a dominant platform among the younger generation, TikTok offers various features that stimulate student creativity in producing Islamic da'wah content. Using a quantitative correlational approach with a sample of 31 KPI students, data were collected through a structured questionnaire and analyzed using SPSS version 25. The Pearson correlation test revealed a very strong and significant relationship between TikTok usage and student creativity (r = 0.909; p < 0.01). The linear regression analysis showed that TikTok usage explains 82.6% of the variance in creativity (R² = 0.826), although the regression model did not produce statistically significant results (p = 0.775). These findings indicate a strong associative relationship but suggest that other external factors may influence creativity. The study highlights the potential of TikTok as a tool to support creative expression and da'wah in the digital age, while recommending further research using multivariate or mixed methods for deeper understanding.